KAJIAN UMPAN BALIK GURU TERHADAP HASIL BELAJAR SISWA - Sofyatiningrum, Etty; Ulumudin, Ikhya; Perwitasari, Farah (Pusat Asesmen dan Pembelajaran, 2019)
The purpose of this study was to identify the form of feedback on the learning outcomes on 8th graders junior high school conducted by the teacher. The study was conducted in the city of Yogyakarta, Makassar, Bandung and Badung during July-August 2019. Respondents were 8th grade junior high school teachers, who teach Science and English subjects. School samples were purposely taken from students who achieve high scores in the UN. Respondents were observed during the learning process followed by interviews and discussion with other teacher. The results of the study show that the implementation of teacher feedback on student learning outcomes has not yet optimal. This is indicated by the teacher's comments on student learning outcomes only correcting mistakes, and giving the correct answers. Almost all teachers have not provide depth explanation nor additional concepts towards the mistakes in order to strengthen students’ understanding. According to respondents, there are contributing factors in giving feedbacks on the learning outcomes. These are: (1) teachers’ knowledge on the meaning and function of feedback on student learning outcomes; (2) there is no guidance from the government regarding the importance of teacher feedback, and (3) there is no training from the government about feedback. To foster teachers’ feedback on student learning outcomes requires government efforts with clear guidelines about the necessity to emphasize feedback on student learning outcomes.